Relation between the compaction rate and physical and mechanical properties of particleboards - Dias,Fabricio Moura (2005)
The compaction rate, the relation between the density of the wood panel and the density of the wood used for producing the particles, is an indicator of the product's densification. Among the various types of wood panels, particleboards are widely employed in the lumber industry, mainly for the furniture production. This paper presents a study of the relation between the compaction rate and the properties of tensile strength perpendicular to surface, Modulus of Rupture (MOR) and Modulus of Elasticity (MOE) obtained from a static bending test, thickness swelling and water absorption (2 and 24 hours). These properties were calculated according to the Brazilian ABNT, NBR 14810 standard. Particleboards were produced using the species Pinus elliotti and adhesive ureaformaldehyde. The relation was established by a multiple linear regression, and the most appropriate statistical models were determined. The estimated models indicate statistically significant effects of water absorption in 2 hours and MOR in the particleboards' compaction rate.